Polacy w Białoruskiej Socjalistycznej Republice Sowieckiej 1986–1991. Wybrane aspekty - Gawin, Tadeusz (Polityka i Społeczeństwo, 2021)
The article is an attempt at presenting the ways in which the Polish People’s Repub-lic’s and the Third Polish Republic’s authorities took advantage of the Gorbatschev’s perestroika in the USSR as well as of the new intellectual currents in Poland to help the Poles in the USSR to pursue their national revival. The text is based on archival documents (mainly from Archiwum Akt Nowych, zespół Wydział Zagraniczny Komitetu Centralnego PZPR) as well as an analysis of the most recent publications concerning the issue. The article first aims at answering the questions how the Poles in Belarus used the offered support in 1988–1991 and if they managed to lay foundations for the future Polish activity in Belarus. Second, it tries to assess if and to what extent the Poles living in Poland were involved in the authorities’ actions for the benefit of their compatriots in Belarus.